2023
DOI: 10.3389/fcvm.2022.1021934
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosignals in abdominal aortic aneurysms

Abstract: Cumulative evidence has shown that mechanical and frictional forces exert distinct effects in the multi-cellular aortic layers and play a significant role in the development of abdominal aortic aneurysms (AAA). These mechanical cues collectively trigger signaling cascades relying on mechanosensory cellular hubs that regulate vascular remodeling programs leading to the exaggerated degradation of the extracellular matrix (ECM), culminating in lethal aortic rupture. In this review, we provide an update and summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 132 publications
0
10
0
Order By: Relevance
“…8 It was also demonstrated that macrophage-derived signals could regulate the expression of Piezo-1 by the vascular smooth muscle cells in the aorta and that this could play a critical role during vascular matrix remodeling. 9,10 To assess the direct role of macrophage-derived Piezo-1 in adjusting the angiogenic response following hindlimb ischemia, mice with conditional knockdown of Piezo-1 in the myeloid lineage (Piezo1 flox/flox LysM Cre ) were generated. The authors demonstrated that the deficiency of Piezo-1 in myeloid cells improved the reperfusion of blood in the leg of mice after hindlimb ischemia by facilitating the revascularization response locally.…”
Section: See Accompanying Article On Page 504mentioning
confidence: 99%
See 1 more Smart Citation
“…8 It was also demonstrated that macrophage-derived signals could regulate the expression of Piezo-1 by the vascular smooth muscle cells in the aorta and that this could play a critical role during vascular matrix remodeling. 9,10 To assess the direct role of macrophage-derived Piezo-1 in adjusting the angiogenic response following hindlimb ischemia, mice with conditional knockdown of Piezo-1 in the myeloid lineage (Piezo1 flox/flox LysM Cre ) were generated. The authors demonstrated that the deficiency of Piezo-1 in myeloid cells improved the reperfusion of blood in the leg of mice after hindlimb ischemia by facilitating the revascularization response locally.…”
Section: See Accompanying Article On Page 504mentioning
confidence: 99%
“…8 It was also demonstrated that macrophage-derived signals could regulate the expression of Piezo-1 by the vascular smooth muscle cells in the aorta and that this could play a critical role during vascular matrix remodeling. 9,10…”
mentioning
confidence: 99%
“…Whether VSMCs possess a similar response to ECM rigidity remains unknown, however, VSMCs possess numerous stretch activated ion channels including piezo1 and members of the TRP (transient receptor potential) family (Lowis et al, 2023). In normal physiology, these channels are activated transiently by blood flow derived stretching of the aortic wall (Liu & Lin, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…SAC activation enables mechanical stimuli to be converted into biochemical responses through mediating the diffusion of ions, including calcium ions (Ca 2+ ), across the cell membrane (Kobayashi & Sokabe, 2010). Whether VSMCs possess a similar response to ECM rigidity remains unknown, however, VSMCs possess numerous stretch activated ion channels including piezo1 and members of the TRP (transient receptor potential) family (Lowis et al, 2023). In normal physiology, these channels are activated transiently by blood flow derived stretching of the aortic wall (Liu & Lin, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…SAC activation enables mechanical stimuli to be converted into biochemical responses through mediating the diffusion of ions, including calcium, across the cell membrane (Kobayashi and Sokabe, 2010). Whether VSMCs possess a similar response to ECM rigidity remains unknown, however, VSMCs possess numerous stretch activated ion channels including piezo1 and members of the TRP (transient receptor potential) family (Lowis et al, 2023). In normal physiology, these channels are activated transiently by blood flow derived stretching of the aortic wall (Liu and Lin, 2022).…”
Section: Introductionmentioning
confidence: 99%